Getting students to believe in themselves. (February 2017) - Saphier, Jon
Surrounding students with messages that they have the ability to learn and teaching them how is at the core of closing the achievement gap. Teachers can engage in verbal behaviors that counteract the negative messages that children of color receive outside the classroom. Those verbal behaviors can embed these messages for students: What we're doing is important; you can do it; and I'm not going to give up on you. The author introduces three classroom patterns that teachers can use to deliver those messages to students: persevere and return, giving help, and positive framing of reteaching. The article also includes a list of 50 ways to get students to believe in themselves and take ownership of their learning .